Outcomes of Recreational Activity-Associated Trauma in Elderly Persons on Blood-Thinning Medications. Issue 4 (April 2017) - Deboard, Zachary M.; Grotts, Jonathan; Ferrigno, Lisa
With increasing life expectancy, the elderly are participating in recreational activities traditionally pursued by younger persons. Elderly patients have many reasons for worse outcomes after trauma, one of which may be the rising use of anticoagulant and/or antiplatelet medications. This study aimed to determine whether preinjury use of these agents yielded worse outcomes in geriatric patients injured during high-impact recreational activities. The National Trauma Data Bank was reviewed from 2007 to 2010 for patients ≥65 years admitted to Level I or II trauma centers with ICD-9 E-codes for specific mechanisms of injury. These included motorcycles, bicycles, snowmobiles, all-terrain vehicles, equestrian, water and alpine skiing, snowboarding, and others. Patients with preinjury bleeding disorder (BD), including warfarin and clopidogrel use, were compared with controls via a coarsened exact matching analysis. BD patients (294) were compared with 3929 controls. Although increased in BD patients, no significant mortality differences were observed in unmatched or matched analyses. BD patients yielded greater hospital length of stay (5 vs 4 days, P = 0.020) with increased odds of receiving five units or more of blood (7.0% vs 2.1%, odds ratio = 4.7, P < 0.001) and of deep vein thrombosis (7.6% vs 3.8%, odds ratio = 2.1, P = 0.018). Elderly patients with BD, including warfarin or clopidogrel use, do not seem to have significantly increased mortality after injury during specified recreational activities. BD patients had greater hospital length of stay, transfusion requirements, and deep vein thrombosis rates. These findings may inform counseling for those taking such medications as to the potential for adverse outcomes.